Azathioprine induced liver disease: nodular regenerative hyperplasia of the liver and perivenous fibrosis in a patient treated for multiple sclerosis. Issue 6 (June 1991) - Mion, F; Napoleon, B; Berger, F; Chevallier, M; Bonvoisin, S; Descos, L
Abstract : Azathioprine hepatotoxicity has been described mainly in renal transplant recipients. Most reported cases are related to lesions of the venous system of the liver: peliosis hepatis, veno-occlusive disease of the liver, perisinusoidal fibrosis, and nodular regenerative hyperplasia of the liver. The most common clinical manifestation of these hepatic vascular lesions is portal hypertension. We present a case of nodular regenerative hyperplasia and perivenous fibrosis in a patient receiving azathioprine for multiple sclerosis. Histological abnormalities were similar to those described in renal transplant patients, and azathioprine was the only potential hepatotoxic agent present.